Self-Assembling Toroidal Cell Constructs for Tissue Engineering Applications. (April 2022) - Worden, Austin; Uline, Mark J.; Shazly, Tarek; Stern, Matt; Potts, Jay D.
Abstract: Developing tissues have intricate, three-dimensional (3D) organizations of cells and extracellular matrix (ECM) that provide the framework necessary to meet morphogenic and necessary demands. Migrating cells, in vivo, are exposed to numerous conflicting signals: chemokines, ECM, growth factors, and physical forces. While most of these have been studied individually in vivo or in vitro, our understanding of how cells integrate these various signals is lacking. We previously developed a novel self-organizing cellularized collagen hydrogel model that is adaptable, tunable, reproducible, and capable of mimicking the multitude of stimuli that cells experience. Our model produced self-assembled toroids of cells that were formed by 24 h. Data we present here show toroids initially form as early as 3 h after seeding. Additionally, toroids formed when cells were seeded on various collagen subtypes and were sensitive to the composition of the hydrogel. Moreover, we found differences in remodeling in toroid gels compared to gels with cells embedded in them using both a collagen binding peptide and rheology. Using scanning electron microscopy, we observed toroids forming a crater-like structure compared to whole gel contractions in mixed in gels. Finally, when multiple cells were mixed prior to seeding, heterogeneous toroids formed with some containing clusters of cells.